Response of rhizosphere microbial community structure and production performance of corn and soybean to belt planting mode - Wang, Guihua; Feng, Shilin; Han, Xiaodong; Zheng, Hui; Bai, Chunhua; Li, Guoqing; Zhao, Guofen (Frontiers in Sustainable Food Systems, 2024)
Soybean and corn strip cropping takes full advantage of the root characteristics and plant height differences between soybean and corn, which can improve crop photosynthesis and nutrient uptake as well as capitalize on the marginal effect of corn. However, there is not enough in-depth research on the effects of soybean and corn strip cropping modes on inter-root microbial communities and crop yield traits and their correlations, and the functional genes of inter-root microbes. In this study, the structural composition and functional genes of soil inter-root microbial communities under different strip cropping patterns of soybean and maize, Mode 1, Mode 2, and Mode 3, were studied using macro-genome high-throughput sequencing, and the yield traits of soybean and maize were determined and the correlation was understood, taking Zhonglian Soybean 1505 and Tiyu 108 maize as test materials at the experimental base of the Research Institute of Agricultural and Livestock Sciences, Xing'anmeng, Inner Mongolia. correlation between the two. The following results were found. Redundancy analysis found that rhizosphere microorganisms are mainly bacteria, followed by viruses, followed by archaea, and fungi are the least. Relatively speaking, viruses and bacteria are more susceptible to the influence of planting patterns than fungi. Alpha diversity analysis shows that the diversity index changes significantly during the peak flowering period. There is no difference between the other two stages. The diversity of maize rhizosphere microorganisms under Mode 1 or Mode 2 modes is higher than that under Mode 3 modes, while the diversity of soybean rhizosphere microorganisms under Mode 3 modes is higher than the other two modes. Profiling analysis found that different growth periods and planting patterns lead to varying degrees of changes in community structure. The dominant bacterial phyla include Pseudomonas, Actinobacteria, Bacteroidetes, and Streptococcus. The dominant genera of bacteria are rhizobia, pseudomonas, erythrobacteria, and pseudomonas. The relative abundance of slow root rhizobia in the three growth stages of maize rhizosphere is relatively low. The results of yield traits showed that corn yield under Mode 1 and Mode 2 planting was significantly higher than that under pattern III; soybean yield under pattern III planting was significantly higher than that under the other two patterns, indicating that pattern I or II planting is suitable for corn production, while Mode 3 planting mode is more suitable for soybean production. Correlation analysis showed that S_Massilis_putida was significantly and positively correlated with maize yield, and S_lysobacter_capsici was highly significantly and significantly positively correlated with the number of soybean plants per square meter, and the number of plants in 2 square meters. This study contributes to our further understanding of the classification of inter-root microorganisms and their functional relationships in maize and soybean under different conditions.